Pembelajaran Ramah Anak bagi Orang Tua dan Guru Taman Kanak-Kanak di Kecamatan Bontotiro - Muh. Yusri Bachtiar; Azizah Amal; Rusmayadi Rusmayadi (Universitas Negeri Makassar, 2019)
his paper is the result of the Community Partnership Program (PKM) activity by presenting the use ofAcrylic Manipulative Aids (APMA) for learning fraction concepts for math teachers. The purpose of the activity isto maximize active learning activities in the classroom and use teaching aids in mathematics learning activities. Thetarget is for junior high school teachers in Bulukumba District where 21 people are involved in the activity. Theform of activities is training, while implementation information is fulfilled by providing worksheets andquestionnaires as response sheets for activities. The results of the training activities carried out received a positiveresponse. Not only is APMA considered feasible as a medium of learning or teaching aids, but it can also be used tohelp students overcome difficulties in learning the concept of fractions, fraction operations consisting of addition,subtraction, multiplication, and division. In addition, by convincing the teacher to respond that APMA can completethe explanations contained in mathematics textbooks. In other words, in addition to learning by using learningresources derived from books, APMA is also useful to supplement the provision of understanding to students in theclassroom.